Pattern of Joint Involvement, Inflammatory Markers, and Autoantibodies Among Rheumatoid Arthritis Patients Attending Rizgary Teaching Hospital - Abdul, Hazha Mohammed; Gliana, Masar (Journal of Sulaimani Medical College, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder. Early initiation of treatment is essential, and the presence of autoantibodies (RF, anti-CCP) and elevated inflammatory markers plays a central role in diagnosis. Objective: This study aims to explore the relationship between joint involvement patterns and inflammatory markers and autoantibody profiles in newly diagnosed RA patients. Patients and Methods: A cross-sectional study was conducted from October 2024 to March 2025 at Rizgary Teaching Hospital in Erbil, Iraq. In this study, 60 recently diagnosed patients with RA, aged 18-70 years old, were included based on the criteria reported on the 2010 ACR/EULAR RA criteria. Patients underwent clinical assessments, including joint involvement patterns and disease activity (DAS28), and laboratory tests for ESR, CRP, RF, and anti-CCP levels. Results: Compared with asymmetrical oligoarthritis, patients with symmetrical polyarthritis had higher ESR and CRP. RF positivity was more frequent in the symmetrical group, while anti-CCP did not differ . In multivariable logistic regression adjusting for age, sex, BMI, disease duration, and ESR, higher CRP and RF positivity independently predicted symmetrical polyarthritis; ESR (p = 0.176) and anti-CCP (p = 0.528) were not independent predictors. Conclusion: CRP and RF are independent correlates of the symmetrical polyarthritis phenotype in early RA, whereas ESR and anti-CCP were not independently associated after adjustment. These findings support integrating CRP and RF with clinical patterns when assessing early disease activity and phenotype
Keywords: Autoantibodies; Diagnosis; Inflammatory markers; Joint involvement; Rheumatoid arthritis